Correlation between TyG index and coronary atherosclerosis assessed by CCTA in elderly male patients: a cross-sectional study - Xiaona wang; Xinqiang Ji; Jianhui yu; Fan wang (Diabetology & Metabolic Syndrome, 2023)
Abstract Background Age is a major risk factor associated with the complexity of coronary artery disease (CAD), and the prognosis of elderly patients with coronary heart disease is relatively poor. Metabolic disturbances are prevalent in the elderly population and contribute to CAD morbidity and mortality. This study aimed to investigate the relationship between the triglyceride-glucose (TyG) index and total coronary atherosclerotic burden assessed non-invasively by Coronary Computed Tomography Angiogram (CCTA) in the elderly population. Methods This retrospective cross-sectional study involved 427 patients who underwent CCTA. The patients were divided into two groups based on their Leiden score: ≥5 and < 5. Comparisons between groups were conducted using t-tests or Mann-Whitney U tests for continuous variables and chi-square tests for categorical variables. The correlation between TyG and Leiden score was assessed using Spearman’s rank correlation coefficient. Univariable and multivariable logistic regression analyses were performed to assess the role of TyG in atherosclerosis risk, using clinical variables previously shown to independently predict a high Leiden score. Results The levels of age and HbA1c% were significantly higher in patients with Leiden score ≥ 5. Patients with Leiden score ≥ 5 showed no significant difference in TyG index compared to those with Leiden score < 5. Pearson correlation analysis showed that HbA1c% (r = 0.44, p < 0.01), age (r = 0.34, p < 0.01), and FBG (r = 0.15, p = 0.01) were positively correlated with Leiden score, while TyG index had no correlation with Leiden score (r = 0.05, p = 0.42). Multiple linear regression analysis showed that HbA1c% (β = 2.92, 95%CI: 2.25–3.56, P < 0.01) was positively correlated with Leiden score, while TyG index had no correlation with Leiden score (β = 0.73, 95%CI: -3.27-4.72, P < 0.01). HbA1c% was found to be an influential factor for obstructive CVD (β = 1.86, 95%CI: 1.50–2.29, P < 0.01), while TyG index was not an independent risk factor for obstructive CVD (β = 0.39, 95%CI: 0.12–1.32, P = 0.13). Conclusion The TyG index did not show any significant correlation with the Leiden score and obstructive CVD as a risk factor in elderly male population. On the other hand, HbA1c% was identified as an influential factor for both the Leiden score and obstructive CVD.